'Recover quicker, train harder, and increase flexibility': massage therapy for elite paracyclists, a mixed-methods study. Issue 1 (26th January 2018) - Kennedy, Ann Blair; Patil, Nirav; Trilk, Jennifer L.
Abstract : Objectives: Massage therapy (MT) enhances recovery by reducing pain and fatigue in able-bodied endurance athletes. In athletes with disabilities, no studies have examined similar MT outcomes, yet participation in sport has increased by >1000 athletes from 1996 to 2016 Olympic games. We examined the effect of MT on pain, sleep, stress, function and performance goals on the bike, as well as quality of life off the bike, in elite paracycling athletes. Methods: This is a quasi-experimental, convergent, parallel, mixed-methods design study of one team, with nine paracycling participants, in years 2015 and 2016. One-hour MT sessions were scheduled one time per week for 4 weeks, and then every other week for the duration of the time the athlete was on the team and/or in the study. Closed and open-ended survey questions investigating athlete goals, stress, sleep, pain and muscle tightness were gathered pre and post each MT session, and every 6 months for health-related quality of life. Quantitative analysis timepoints include baseline, 4–6 months of intervention and final visit. Additional qualitative data were derived from therapists' treatment notes, exit surveys, and follow-up emails from the athletes and therapists. Results: Significant improvement was found for sleep and muscle tightness; quantitative results were reinforced by athlete comments indicating MT assisted in their recovery while in training. There were no improvements in dimensions measuring quality of life; qualitative comments from athletes suggest reasons for lack of improvement. Conclusion: This real-world study provides new information to support MT for recovery in elite paracyclists.